DASAR EDITING VIDEO BERBASIS ANDROID UNTUK KREASI KONTEN MEDIA SOSIAL PADA LINGKUNGAN PELAJAR SMA DI KALIMANTAN BARAT - Muhammad Faqih Dzulqarnain; Muhammad Nazir (Politeknik 'Aisyiyah Pontianak, 2021)
Social media has an important role for various types of information reported. Millennials are increasingly using social media today. One form of news on social media besides pictures is video. Video, which is a multimedia branch, is the main dish. In the context of entertainment, the ability to produce good videos is very necessary. So that it gave birth to a new profession among the millennials to generation Z, namely content creators. In this profession, the main ability that must be possessed is video editing skills. Without video editing, the video that is made looks stiff and unattractive. Moreover, videos that will be posted on social media must attract viewers' interest. To support video editing skills, community service is held on the basics of video editing for content creation on mobile-based social media. This service in the form of a workshop aims to provide basic skills for participants to do video editing using a mobile platform in West Kalimantan in particular. The evaluation of this activity received a good response with a score of 62.8% for the clarity of the material, 54.3% for the suitability of the material and 58.1% for the quality of material delivery. So that the average satisfaction of activity results is 57.1%.